두충 추출물 투여와 트레드밀 운동이 골다공증 유발 백서의 골대사에 미치는 영향 - 윤석주(Seok Joo Yoon); 김경윤(Kyung Yoon Kim); 김계엽(Gye Yeop Kim); 남기원(Ki Won Nam); 심기철(Ki Cheol Sim); 김은정(Eun Jung Kim); 정현우(Hun Woo Chung); 김형우(Hyung Woo Kim); 김기도(Gi Do Kim) (동의생리병리학회지, 2008)
This study classified 40 of 10 weeks-old male Sprague Dawley rats which have osteoporosis caused by glucocorticoid(GC) induction into four groups of 10 rats and made the subjects medicated them Eucommia ulmoides Oliver and participate in treadmill exercise. Group I was non-treatment after GC induction; Group II was treadmill exercise after GC induction; Group III was Eucommia ulmoides Oliver feeding after GC induction; Group IV was treadmill exercise and Eucommia ulmoides Oliver feeding after GC induction. In the bone mineral density and bone strength test, there was a statistically significant difference between the group I, II, III compared to group IV(p<0.05). In the osteocalcin level as one of bone formation indexes, there was a statistically significant difference between the group I, II, III compared to group IV(p<0.05). In respect to the calcium there was a statistically significant difference between group I, II, III compared to group IV(p<0.05). In respect to histological findings, the group IV showed mild femur disruption and lytic change on femur section. The above results suggests that Eucommia ulmoides Oliver medicated and treadmill exercise is effective to prevention and treatment of osteoporosis.